Radiation shielding material having cellular confinement and method of making

CN122976155APending Publication Date: 2026-10-27NANJING UNIV OF AERONAUTICS & ASTRONAUTICS +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611042349.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-14
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,这类高密度填料在聚合物中普遍存在分散困难的问题,尤其是在加工或长期服役过程中,容易发生团聚和沉降,进而引起局部性能不均、应力集中甚至微裂纹的产生

Benefits of technology

与现有核电电缆材料相比,本发明的性能提升主要体现在结构与界面协同作用带来的综合效果,而不是依赖单一材料改性,优点体现在以下几方面:

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122976155A_ABST
    Figure CN122976155A_ABST
Patent Text Reader

Abstract

The application provides a radiation shielding material with a honeycomb confinement and a preparation method thereof, and relates to the technical field of materials.The material comprises: a cross-linked polyethylene insulation layer; a honeycomb confinement structure layer combined on the surface of the cross-linked polyethylene insulation layer; the honeycomb confinement structure layer is composed of a honeycomb skeleton formed by a nanofiber network, and the honeycomb unit of the honeycomb skeleton is filled with high-atomic-number radiation shielding nanoparticles; the honeycomb confinement structure layer further comprises an encapsulation layer, the encapsulation layer is covered on the surface of the honeycomb skeleton filled with the high-atomic-number radiation shielding nanoparticles, and a closed honeycomb shell layer structure is formed.The material no longer depends on modification of a single material, the material is divided into multiple independent units through the honeycomb structure, and a high-density filling area is locally introduced in the interior, so that the stability and the radiation shielding performance of the material are effectively improved, and the mechanical performance is ensured.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of materials technology, and in particular to a radiation shielding material with cellular confinement and its preparation method. Background Technology

[0002] Nuclear power plant cables must withstand multiple coupled effects, including heat, radiation, damp heat, and mechanical stress, during long-term operation. Among these, radiation aging is one of the key factors leading to the deterioration of insulation material performance. Existing nuclear power cable insulation layers mostly use cross-linked polyethylene (XLPE) or low-smoke halogen-free polyolefin materials. Antioxidants, inorganic fillers, or radiation stabilizers are added to improve their radiation resistance, but they do not possess radiation shielding capabilities.

[0003] To enhance radiation shielding capabilities, inorganic fillers or oxides of high atomic number elements (such as Bi₂O₃ and PbO) are typically introduced into the material. However, these high-density fillers generally suffer from dispersion difficulties in polymers, especially during processing or long-term service, where they are prone to agglomeration and sedimentation, leading to localized performance inhomogeneity, stress concentration, and even microcracks. Therefore, how to suppress filler sedimentation while ensuring shielding performance, and also considering the mechanical stability of the material, is a pressing issue that needs to be addressed in the field of nuclear power cables.

[0004] Therefore, this invention is proposed. Summary of the Invention

[0005] To address the aforementioned technical problems, this invention provides a radiation shielding material with honeycomb confinement and its preparation method. This material no longer relies on single-material modification; instead, it divides the material into multiple independent units through a honeycomb structure and introduces high-density filling regions locally within it, thereby effectively improving the material's stability and radiation shielding performance while ensuring its mechanical properties.

[0006] In order to achieve the objective of this invention, the following technical solution is adopted: This invention provides a radiation shielding material with cellular confinement, comprising: Cross-linked polyethylene insulation layer; A honeycomb confinement structure layer composited on the surface of the cross-linked polyethylene insulation layer; The honeycomb confinement structure layer is composed of a honeycomb skeleton made of a nanofiber network, and the honeycomb skeleton is filled with high atomic number radiation shielding nanoparticles. The honeycomb confinement structure layer also includes an encapsulation layer, which covers the surface of the honeycomb skeleton filled with the high atomic number radiation shielding nanoparticles, forming a closed honeycomb shell structure.

[0007] Furthermore, the nanofiber network is composed of a polymer material compatible with cross-linked polyethylene, specifically including a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer.

[0008] Furthermore, the high atomic number radiation shielding nanoparticles are bismuth oxide nanoparticles, and the average particle size of the nanoparticles is 20nm-200nm.

[0009] Furthermore, the thickness of the cellular confinement structure layer is 20μm-100μm, and the pore size of the cellular unit is 5μm-50μm.

[0010] This invention also provides a method for preparing a radiation shielding material with cellular confinement, comprising the following steps: S1. Prepare a cross-linked polyethylene insulation layer; S2. Construct a honeycomb skeleton layer on the surface of the cable insulation layer; S3. Fill the honeycomb cells of the honeycomb skeleton layer with high atomic number radiation shielding nanoparticles. S4. The filled honeycomb skeleton is encapsulated to form a closed honeycomb shell structure.

[0011] Furthermore, in S1, the insulating layer is prepared by extrusion at a temperature of 160-190°C.

[0012] Furthermore, S1 specifically includes: melting polyethylene and uniformly extruding it onto the surface of a copper conductor; subsequently crosslinking the polyethylene surface that has already coated the conductor.

[0013] Furthermore, in S2, a honeycomb skeleton layer is constructed using electrospinning technology. The conditions for electrospinning technology are: applied voltage of 20kV, spray distance of 15cm, propulsion speed of 0.75mL / h, relative humidity of 70%, and a patterned collection device with a micropore array is used to induce the formation of a regular honeycomb unit structure.

[0014] Furthermore, S3 specifically includes: S301. Disperse bismuth oxide nanoparticles in an organic solvent and add a dispersant to form a suspension; S302. Immerse the product obtained in S2 into the suspension and dry it.

[0015] Furthermore, the dispersant is polyvinylpyrrolidone (PVP) dispersant.

[0016] Furthermore, in S4, the encapsulation process is carried out at a temperature of 100°C, a pressure of 3 MPa, and a time of 8 minutes.

[0017] Furthermore, the raw material for the honeycomb skeleton layer is a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer, wherein the mass ratio of low-density polyethylene to ethylene-vinyl acetate copolymer is 7:3. The total mass fraction of the mixture of low-density polyethylene and ethylene-vinyl acetate copolymer in the spinning solution used to prepare the honeycomb skeleton layer is 8%-15%.

[0018] Furthermore, both ethylene and the ethylene-vinyl acetate copolymer were dissolved in a mixed solvent of xylene and tetrahydrofuran.

[0019] Furthermore, the ratio of xylene to THF (tetrahydrofuran) is 7:3, the concentration of xylene is 70%, and the concentration of tetrahydrofuran is 30%.

[0020] The present invention has the following technical effects: Compared with existing nuclear power cable materials, the performance improvement of this invention is mainly reflected in the comprehensive effect brought about by the synergistic effect of structure and interface, rather than relying on the modification of a single material. The advantages are reflected in the following aspects: 1) Regarding the stability of the filler, the honeycomb structure divides the material into multiple independent units, confining the high-density shielding particles within a local space, thus effectively avoiding the sedimentation and stratification problems common in traditional systems. Furthermore, the nano-interface layer on the honeycomb wall surface further enhances the adhesion of the particles, enabling the filler to maintain a relatively stable distribution during long-term use.

[0021] 2) In terms of radiation shielding performance, this structure introduces local high-density filling areas inside the cellular units, allowing rays to enter the high attenuation region multiple times during propagation. At the same time, the cellular structure provides more interfaces, which is beneficial to enhancing the scattering effect, thereby improving the shielding efficiency without significantly increasing the overall density.

[0022] 3) In terms of mechanical properties, the honeycomb structure can disperse stress through unit deformation when under stress, reducing the risk of local stress concentration. At the same time, the multi-interface structure has a certain inhibitory effect on crack propagation. Therefore, while improving the shielding performance, it will not significantly reduce the flexibility and crack resistance of the material.

[0023] 4) In addition, the structure has a certain degree of engineering feasibility, and the relevant preparation processes are all existing mature technologies with a basis for practical application. Attached Figure Description

[0024] To more clearly illustrate the specific embodiments of the present invention or the technical solutions in the prior art, the drawings used in the description of the specific embodiments or the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For those skilled in the art, other drawings can be obtained from these drawings without creative effort.

[0025] Figure 1 Process flow diagram; Figure 2 : The process preparation route; Figure 3 : Microstructure diagram of the prepared material; Figure 4 Traditional uniform filling structure; Figure 5 : Cellular confined structure; Figure 6 : Geometric structure diagram for simulation of geometric conditions; Figure 7 Simulation results; Figure 8 Experimental setup 1; Figure 9 Experimental setup 2; Figure 10 Shielding performance test results; Figure 11 Results of tensile strength test; Figure 12 Results of the elongation at break experiment; Figure 13 : Experimental results of elastic modulus; Figure 14 : Average bending life test results; Figure 15 Minimum bending radius test results. Detailed Implementation

[0026] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be clearly and completely described below. Obviously, the described embodiments are only a part of the embodiments of this invention, and not all of them. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0027] Firstly, the protection of existing nuclear power plant cables in radiation environments mainly relies on the radiation tolerance of the insulation material itself, or on the uniform addition of high atomic number fillers (such as bismuth oxide and tungsten oxide) to a polymer matrix to achieve a certain degree of radiation shielding. However, the above technical approaches still have significant limitations in practical applications, especially in improving radiation shielding capabilities, where the following problems exist.

[0028] First, in existing technologies, high-density shielding fillers are typically added to polymer systems in a uniformly dispersed form. However, due to the high density of materials such as bismuth oxide, sedimentation or localized enrichment can easily occur during melt processing or long-term service, leading to uneven distribution of shielding performance within the material and thus affecting the stability of the overall radiation protection effect. This problem is particularly prominent when cables are laid vertically for extended periods or in high-temperature environments.

[0029] Secondly, in order to improve radiation shielding capability, traditional methods often rely on increasing the filler content. However, when the filler content reaches a certain proportion, the processing fluidity of the material decreases significantly, and it will also cause the mechanical properties of the insulation layer to deteriorate, such as reduced flexibility and increased risk of cracking, thus limiting its application in cable structures.

[0030] Furthermore, existing uniform filling systems mainly rely on a single-penetration attenuation mechanism under radiation, meaning that rays attenuate linearly along the path when passing through the material. This lack of effective control over the ray propagation path results in limited improvement in shielding efficiency under the same material dosage.

[0031] In addition, existing technologies generally lack ideas for improving radiation shielding capabilities from the perspective of structural design, and mostly focus on optimizing material formulations, while the control of the spatial distribution morphology of fillers and interface structure is insufficient, making it difficult to achieve a balance between shielding efficiency and material performance.

[0032] Based on the above problems, the present invention aims to propose a method that combines structural confinement and interface control to improve the space utilization efficiency of high-density fillers without significantly increasing the total filler volume, and enhance the multiple scattering and absorption of radiation within the material, thereby effectively improving the radiation shielding capability of cable insulation layers, while taking into account the mechanical and processing properties of the material.

[0033] This invention provides a radiation shielding material with cellular confinement, comprising: Cross-linked polyethylene insulation layer; A honeycomb confinement structure layer composited on the surface of the cross-linked polyethylene insulation layer; The honeycomb confinement structure layer is composed of a honeycomb skeleton made of a nanofiber network, and the honeycomb skeleton is filled with high atomic number radiation shielding nanoparticles. The honeycomb confinement structure layer also includes an encapsulation layer, which covers the surface of the honeycomb skeleton filled with the high atomic number radiation shielding nanoparticles, forming a closed honeycomb shell structure.

[0034] In terms of structural design, a honeycomb structure is introduced into the cable sheath system and used to spatially confine the high-density filler, transforming the filler from a traditional continuous distribution to a discrete unit distribution, thus solving the settlement problem from a structural perspective.

[0035] Secondly, at the interface level, a nanoscale functional interface is constructed on the surface of the honeycomb wall, so that the structural unit not only plays a supporting role, but also has the ability to control the interface of particles, thereby stabilizing the position of the filler at the microscale.

[0036] This design effectively ensures that particles are confined within independent units, preventing sedimentation and agglomeration. The encapsulation layer effectively enhances structural stability. Multiple-interface scattering enhances radiation shielding efficiency without increasing the overall material density. Furthermore, the honeycomb structure disperses stress through unit wall deformation under load, reducing stress concentration. By combining the honeycomb structure, nano-interfaces, and shielding filler, synergistic optimization of anti-settling performance, shielding performance, and mechanical properties is achieved. This improves the space utilization efficiency of high-density filler without significantly increasing the total filler volume, and enhances multiple scattering and absorption of radiation within the material. Consequently, it effectively improves the radiation shielding capability of cable insulation while also considering the material's mechanical and processing properties.

[0037] In some embodiments, the nanofiber network is composed of a polymeric material compatible with cross-linked polyethylene, specifically including a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer.

[0038] Low-density polyethylene (LDPE) and cross-linked polyethylene (XLPE) have similar chemical structures and good compatibility, ensuring interlayer bonding. Meanwhile, the polar vinyl acetate groups in ethylene-vinyl acetate copolymer (EVA) enhance interaction with polar solvents or fillers, facilitating electrospinning and subsequent particle adhesion. Blending low-density polyethylene and ethylene-vinyl acetate copolymer can adjust the viscosity of the spinning solution, fiber diameter, and honeycomb structure formation.

[0039] This further achieves a strong interfacial bond between the honeycomb skeleton layer and the XLPE insulation layer, preventing peeling and improving the operability and structural regularity of the electrospinning process.

[0040] In some embodiments, the high atomic number radiation shielding nanoparticles are bismuth oxide nanoparticles, and the average particle size of the nanoparticles is 20 nm-200 nm.

[0041] Bismuth atoms exhibit a high mass attenuation coefficient for photons. Using bismuth oxide with a nanoscale particle size facilitates more uniform filling within the honeycomb unit, and the large specific surface area per unit mass of particles increases the probability of interaction with radiation. Simultaneously, this particle size range ensures that the bismuth oxide nanoparticles are smaller than the pore size of the honeycomb unit, guaranteeing that the particles can enter the pores.

[0042] In some embodiments, the thickness of the cellular confinement structure layer is 20μm-100μm, and the aperture of the cellular cell is 5μm-50μm.

[0043] The thickness of this structural layer determines the total mass thickness of the shielding layer and affects the radiation attenuation rate; the aperture size of the cellular cells affects the cell confinement effect, particle filling uniformity, and the number of scattering events between cells. This numerical constraint ensures effective shielding within a given thickness range without significantly increasing the cable's outer diameter and weight; it also ensures that the aperture size matches the nanoparticle size, guaranteeing sufficient filling and preventing particle escape.

[0044] Secondly, the present invention also provides a method for preparing a radiation shielding material with a cellular confinement, comprising the following steps: S1. Prepare a cross-linked polyethylene insulation layer; S2. Construct a honeycomb skeleton layer on the surface of the cable insulation layer; S3. Fill the honeycomb cells of the honeycomb skeleton layer with high atomic number radiation shielding nanoparticles. S4. The filled honeycomb skeleton is encapsulated to form a closed honeycomb shell structure.

[0045] This construction process first forms an insulating matrix, then constructs a porous framework, introduces functional particles, and finally seals them, ensuring that the particles remain within the honeycomb pores and do not penetrate the insulating layer, thus avoiding sacrifice of insulation performance. Simultaneously, the encapsulation step achieves fusion bonding between fibers, creating a physical confinement of the particles. This ensures structure-function integration, allows for independent optimization of the process window for each step, and avoids the negative impact of fillers on the electrical and mechanical properties of the insulating layer found in traditional blending methods.

[0046] In some embodiments, in step S1, the insulating layer is prepared by extrusion at a temperature of 160-190°C.

[0047] This temperature range allows the polyethylene to fully melt and flow while preventing thermal degradation and ensuring a uniform thickness of insulation layer covering the conductor after extrusion. This step guarantees a controllable thickness and smooth surface of the insulation layer, providing a good substrate for subsequent honeycomb structures.

[0048] In some embodiments, S1 specifically includes: melting polyethylene and uniformly extruding it onto the surface of a copper conductor; subsequently crosslinking the polyethylene surface that has already coated the conductor.

[0049] In some embodiments, in S2, a honeycomb skeleton layer is constructed using electrospinning technology. The conditions for electrospinning technology are: applied voltage of 20kV, spray distance of 15cm, propulsion speed of 0.75mL / h, relative humidity of 70%, and a patterned collection device with a micropore array is used to induce the formation of a regular honeycomb cell structure.

[0050] This structure ensures the formation of a honeycomb skeleton with uniform pore size and regular cell arrangement, while also allowing for adjustment of thickness and pore size through parameters.

[0051] In some embodiments, S3 specifically includes: S301. Disperse bismuth oxide nanoparticles in an organic solvent and add a dispersant to form a suspension; S302. Immerse the product obtained in S2 into the suspension and dry it.

[0052] In some embodiments, the dispersant is a PVP dispersant.

[0053] In some embodiments, in step S4, the encapsulation process is carried out at a temperature of 100°C, a pressure of 3 MPa, and a time of 8 minutes.

[0054] In some embodiments, the raw material for the honeycomb skeleton layer is a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer, wherein the mass ratio of low-density polyethylene to ethylene-vinyl acetate copolymer is 7:3; The total mass fraction of the mixture of low-density polyethylene and ethylene-vinyl acetate copolymer in the spinning solution used to prepare the honeycomb skeleton layer is 8%-15%.

[0055] Low-temperature hot pressing softens the surface of the fiber network and causes localized melting, forming a continuous thin film layer on the surface while maintaining most of the honeycomb pore structure. Simultaneously, the pressure ensures tighter contact between fibers, promoting fusion bonding. This guarantees the formation of a closed shell, preventing particle detachment during use; it also keeps the temperature below the melting point of polyethylene, avoiding damage to the overall honeycomb structure.

[0056] At the same time, the amount of raw material used in the honeycomb skeleton layer is limited to ensure continuous fibers and uniform pore size; it also prevents the fibers from being too fine and the structure from collapsing if the concentration is too low, or the fibers from being too coarse and the porosity from decreasing if the concentration is too high.

[0057] In some embodiments, both ethylene and the ethylene-vinyl acetate copolymer are dissolved in a mixed solvent of xylene and tetrahydrofuran.

[0058] In some embodiments, the ratio of xylene to tetrahydrofuran is 7:3.

[0059] The following is a detailed explanation using specific embodiments: Example 1 Preparation process as follows Figures 1-2 As shown (1) Preparation of cross-linked polyethylene insulation layer using conventional extrusion process: Multi-strand copper conductor is selected as the conductor, and a cross-linked polyethylene insulation layer is applied to the outside. First, cross-linkable polyethylene material is extruded onto the surface of the conductor, and then cross-linking treatment is performed. The thickness of the insulation layer is controlled at 2 mm. The extrusion temperature is controlled at 160-190℃. Subsequently, cross-linking treatment is completed by peroxide cross-linking or irradiation cross-linking to form a stable three-dimensional network structure in the insulation layer. To improve the adhesion of the subsequent fiber layer, the outer surface of the insulation layer can be lightly surface-treated by solvent wiping to give it certain surface activity or adhesion ability.

[0060] (2) The honeycomb skeleton layer was constructed using electrospinning technology: a low-density polyethylene (LDPE) / ethylene-vinyl acetate copolymer (EVA) blend was used as the spinning material, with a mass ratio controlled at 7:3. This was dissolved in a xylene / tetrahydrofuran (THF) mixed solvent, where the volume ratio of xylene to THF was 7:3, forming a spinning solution with a mass fraction of 12 wt%. The solution was magnetically stirred at 55°C for 5 hours until completely dissolved. During electrospinning, the applied voltage was controlled at 20 kV, the spray distance was 15 cm, and the propulsion speed was approximately 0.75 mL / h. To induce the formation of the honeycomb structure, the relative humidity was controlled at 70%. The breathing effect under high humidity was utilized to induce the formation of a regular honeycomb pore structure during solvent evaporation. Simultaneously, a patterned collection device with a micropore array could be used to allow fibers to preferentially aggregate along specific regions during deposition, thereby obtaining a more regular honeycomb unit structure. Finally, a honeycomb nanofiber network layer with a thickness of about 20-100 μm is formed on the surface of the insulating layer, with a pore size generally in the range of 5-50 μm.

[0061] (3) After the honeycomb structure is constructed, bismuth oxide filler is introduced: the filling is achieved by impregnation. Bi2O3 nanoparticles with an average particle size of 50-200 nm are dispersed in an ethanol solution, PVP dispersant is added, and a stable suspension is formed by ultrasonic dispersion for 60 min. Then the product layer prepared in step (2) is immersed in the suspension for 30 min to allow the solution to fully penetrate into the honeycomb pores. After removal, it is dried at 70 °C for 4 h to fix the particles in the pore structure.

[0062] (4) To improve structural stability, the filler is encapsulated after introduction. A low-temperature hot-pressing treatment at 100℃ (approximately 3 MPa pressure, 8 min) is used to induce localized melting and bonding between the fibers, thereby forming a closed honeycomb shell structure. The resulting structure is shown below. Figure 3 As shown.

[0063] Experimental Example 1 To verify the effect of the honeycomb confinement structure of the present invention on the stable distribution of high-density fillers, the surface and cross-sectional morphology of the traditional uniform filling structure and the honeycomb confinement structure were compared and analyzed.

[0064] Figures 4-5 These are SEM morphology comparison images of a traditional uniformly filled structure and a honeycomb confined structure. Figure 4 It is a traditional uniform filling structure. Figure 5 The structure is a honeycomb confined structure. SEM observation revealed that crack propagation was more pronounced in the traditional uniformly filled structure, with some cracks being quite wide and exhibiting a continuous penetrating trend, indicating significant stress concentration in localized areas within the material. Simultaneously, the poor uniformity around local defects suggests that the high-density filler may experience some degree of local enrichment or interfacial instability within the matrix.

[0065] In contrast, the crack propagation path in the honeycomb confined structure is more tortuous and exhibits a dispersed characteristic. The crack shows significant deflection and interruption during propagation, failing to form a large-scale continuous penetrating region. This indicates that the honeycomb structure can hinder crack propagation through multiple interfaces and local unit structures, thereby achieving stress dispersion. Furthermore, the honeycomb structure exhibits good overall morphological uniformity, with no obvious large-scale defect regions observed. This suggests that the structure is beneficial for improving the distribution stability of high-density fillers in the material and can, to some extent, suppress the local enrichment and delamination problems common in traditional systems.

[0066] Further analysis suggests that the honeycomb confinement structure, by confining the filler within multiple discrete micro-regions, can reduce the tendency of large-scale particle migration. At the same time, the nanofiber interface on the honeycomb wall surface can enhance particle adhesion, which is beneficial to suppressing the sedimentation and local enrichment phenomena commonly found in traditional high-density filler systems, maintaining the stability of the internal structure of the material, and improving the long-term service reliability of the cable insulation layer.

[0067] In addition, the porous honeycomb structure can improve the uniformity of particle spatial distribution, making fuller use of high-density fillers in the insulation layer and providing a structural basis for subsequent improvement of radiation shielding performance.

[0068] Experiment Example 2: Shielding Performance Verification 1) Simulation section 1. Calculation method for radiation shielding performance of materials In particle transport simulation, the first step is to set up a radioactive source to release... By using X-rays and a lead-shielded chamber method to establish a low-background environment, the radiation dose deposited in the detector area after passing through a composite material of a certain thickness was simulated, thereby evaluating the composite material. X-ray radiation shielding performance. A quantitative correlation model between material composition and shielding performance is established using core parameters such as transmittance and equivalent lead weight.

[0069] 2. Setting up the radioactive source According to project requirements, a Co-60 radioactive source was used as... Source of radiation The main energies of the radiation are 1.17 MeV and 1.33 MeV. The radiation source is the 1.33 MeV gamma ray, which has the highest energy, and it emits radiation in one direction.

[0070] 3. Geometric Conditions: The simulated geometric structure is set as follows: Figure 6 As shown Single energy A point source emits radiation into the detector in a unidirectional emission mode through collimated aperture constraint. A cylindrical lead shield (2 cm thick, 20 cm axial length) is placed around the radiation source to absorb Compton scattering and ambient background radiation, reducing the scattered photon flux in the detection area to 10% of its initial value. -3 To evaluate the radiation shielding performance of a composite material placed between a radiation source and a detector, a simulation was conducted. Throughout the simulation, the distance between the radiation source and detector, and the distance between the bottom of the shielding material and the top of the detector, remained constant. The effective dose in the detector grid region after shielding with the sample under evaluation was recorded. .

[0071] 4. Shielding rate calculation (1) Transmittance Rays may be absorbed by materials or their direction of motion may be altered by scattering, causing them to deviate from the original beam. Therefore, Any interaction between radiation and matter will cause The ray is removed from the original beam and cannot reach the point detector. Let the number of beams reaching the detector per unit time and per unit area within the original beam be... The radiation dose is It did not interact with the radiation shielding material and remained in place before the original beam reached the detector. The number of rays is ,but X-ray transmittance for: (2.1) After passing through materials of the same thickness The higher the transmittance of rays, the weaker the radiation shielding performance of the material.

[0072] (2) Linear attenuation coefficient Suppose there is a certain depth in the radiation shielding material No interaction occurred and the beam remained in the original beam. The number of rays is Then in Changes within the material layer due to interactions The ray count is: (2.2) In the formula It is called the linear attenuation coefficient. The total probability of various interactions occurring when a ray passes through a material layer of unit thickness. Integrating equation (2.2) yields the narrow-beam monoenergetic radiation. The exponential decay law of X-rays includes: (2.3) Obviously, substituting equation (2.1) into equation (2.3) yields... X-ray transmittance The relationship with the linear attenuation coefficient is as follows: (2.4) In the simulation, the materials are calculated under different thicknesses. The linear attenuation coefficient of a material can be obtained by fitting the radiation transmittance using the least squares method. Dividing the linear attenuation coefficient by the material density yields the mass attenuation coefficient, which can also be used to evaluate the radiation shielding performance of materials of the same mass.

[0073] 2) Sample verification To verify the actual shielding effect of the sample, measurements were performed using a high-purity germanium gamma spectrometer. Figure 8-9 As shown.

[0074] First, background measurements were performed: Environmental background energy spectra and count rates were collected without a radioactive source. Then, unshielded measurements were performed: Co-60 was used as the radioactive source; the source was placed and the sample was removed, and data were collected. The energy spectrum of directly incident radiation was recorded, along with the corresponding count rate. Subsequently, shielded measurements were performed: the sample was placed between the radiation source and the detector. The radioactive source is located behind the sample, and the energy spectrum and count rate after penetrating the sample are collected. The figure shows an HPGe detector receiving the energy after penetrating the sample at a specific distance. X-rays. Characteristic features were compared under shielded and unshielded conditions. The difference in the count rate of the full-energy X-ray peaks can be used to quantitatively assess the sample's response to a specific energy. The shielding effectiveness of radiation.

[0075] The shielding performance was tested through simulation and experiments. In the simulation, a geometric model of the cable insulation layer with cellular-confined nano-bismuth oxide radiation shielding was constructed, and its shielding performance was simulated and optimized. The influence of the cellular structure on the material's radiation shielding performance was discussed. Simulation results are as follows: Figure 7 As shown, the experimental results are as follows: Figure 10 As shown in the simulation and experimental results, under the same mass conditions, the honeycomb structure exhibits superior radiation shielding performance compared to the traditional uniformly filled structure. This is primarily due to its ability to synergistically control the spatial distribution of the high-density shielding filler and the ray propagation path. In traditional non-honeycomb structures, shielding particles such as bismuth oxide are typically uniformly dispersed within the polymer, and rays primarily penetrate the material along relatively straight lines, with attenuation mainly characterized by single-pass linear absorption. In contrast, the honeycomb structure, by confining high atomic number fillers within multiple discrete honeycomb units, forms a high-density shielding region in a localized area, making it easier for rays to repeatedly enter the high-attenuation region during propagation. Simultaneously, the honeycomb walls and multi-interface structure increase the probability of ray scattering and path deflection, extending the effective propagation path of rays within the material, thereby enhancing photoelectric absorption and Compton scattering effects, and improving overall energy attenuation efficiency. Furthermore, the honeycomb structure can reduce ineffective filler accumulation while maintaining shielding performance, resulting in higher utilization of the high-density filler. Therefore, under the same filler content conditions, its radiation shielding capability is generally superior to that of the traditional non-honeycomb uniformly filled structure.

[0076] Experiment Example 3: Mechanical Property Testing 1. Tensile property test (1) Tensile strength To verify the influence of the honeycomb confinement structure on the mechanical properties of cable insulation, tensile properties were tested on pure XLPE, traditional uniform Bi2O3 filled structure, and honeycomb confinement Bi2O3 structure. The experiments were conducted according to GB / T 1040 standard using an electronic universal testing machine at room temperature. The tensile rate was set to 50 mm / min. Five parallel samples were tested in each group, and the average value was used for analysis. The experimental results are shown below. Figure 11 As shown in Table 1.

[0077] Table 1: Tensile Strength Results The results show that the tensile strength of the material decreases significantly after conventional uniform filling with Bi2O3. This is mainly because high-density particles tend to agglomerate within the polymer, forming localized stress concentration areas that easily induce crack propagation during tensile testing. In contrast, the honeycomb confined structure, by confining Bi2O3 within discrete honeycomb units, reduces large-scale agglomeration between particles. Furthermore, the honeycomb framework disperses stress, resulting in tensile strength that is not only higher than that of the uniformly filled structure but also slightly higher than that of pure XLPE material.

[0078] (2) Elongation at break The experimental results after taking the average value are as follows: Figure 11 As shown in Table 2.

[0079] Table 2: Elongation at Break The results show that traditional uniformly filled structures significantly reduce the material's flexibility, with elongation at break decreasing by nearly 50%. This is because the large amount of inorganic particles restricts polymer chain movement and exacerbates interfacial defects. In contrast, the honeycomb structure, due to its locally confined filling method, maintains better integrity of the continuous polymer phase. Furthermore, the honeycomb structure can absorb some strain through unit deformation during stretching, thus significantly improving its elongation at break and exhibiting superior flexibility.

[0080] (3) Elastic modulus The experimental results after taking the average value are as follows: Figure 13 As shown in Table 3.

[0081] Table 3: Experimental Results of Elastic Modulus Experimental results show that the uniformly filled structure has the highest elastic modulus, but the material becomes significantly harder and more brittle; while the honeycomb confined structure, although having a slightly higher modulus, still maintains good flexibility. This indicates that the honeycomb structure does not simply rely on increasing rigidity to achieve reinforcement, but rather improves the material's toughness while maintaining a certain mechanical support capacity.

[0082] 2. Cyclic bending test Because nuclear power plant cables are subjected to bending, vibration, and complex stress environments during actual service, cyclic bending tests were further conducted on different structures to evaluate their crack resistance and structural stability. A fixed bending radius cyclic loading method was used in the experiment, and the number of cycles corresponding to the appearance of obvious cracks was recorded. Five parallel samples were tested in each group. The average experimental results are shown below. Figure 14 As shown in Table 4.

[0083] Table 4: Results of Cyclic Bending Experiment The results show that the bending life of the material significantly decreases after conventional uniform filling with Bi2O3. This is mainly because stress concentration easily forms in the agglomerated areas of the filler during cyclic bending, leading to the initiation and propagation of microcracks. In contrast, the honeycomb confined structure, with its porous honeycomb units, can buffer stress through local structural deformation during loading. Furthermore, the honeycomb walls and nanofiber interfaces provide some resistance to crack propagation, thus significantly improving its cyclic bending life.

[0084] 3. Minimum bending radius test Further testing of material flexibility was conducted, measuring the minimum allowable bending radius of the sample without cracking. The average experimental results are shown below. Figure 15 As shown in Table 5.

[0085] Table 5: Minimum Bending Radius Test Results Experimental results show that the traditional uniformly filled structure exhibits a significant decrease in the material's bending capacity due to the high rigidity of the particles; while the honeycomb confined structure demonstrates superior flexibility, with a minimum bending radius even better than that of pure XLPE. This indicates that the honeycomb structure can disperse local stress through unit deformation during bending, thereby improving the overall flexibility of the material.

[0086] The combined tensile and bending test results show that while traditional uniform filling with high-density shielding particles can improve shielding capability to a certain extent, it easily leads to material embrittlement, decreased flexibility, and stress concentration. The honeycomb confinement structure proposed in this invention, through the synergistic effect of "structural confinement + nano-interface regulation," enables the stable distribution of Bi2O3 particles within a local space. Simultaneously, the honeycomb unit structure achieves stress dispersion and crack prevention, thereby improving radiation shielding capability while maintaining superior mechanical properties and flexibility, demonstrating the advantages of integrated structural and functional design.

[0087] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, and not to limit them; although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some or all of the technical features; and these modifications or substitutions do not cause the essence of the corresponding technical solutions to deviate from the technical solutions of the embodiments of the present invention.

Claims

1. A radiation shielding material with honeycomb confinement, characterized in that, include: Cross-linked polyethylene insulation layer; A honeycomb confinement structure layer composited on the surface of the cross-linked polyethylene insulation layer; The honeycomb confinement structure layer is composed of a honeycomb skeleton made of a nanofiber network, and the honeycomb skeleton is filled with high atomic number radiation shielding nanoparticles. The honeycomb confinement structure layer also includes an encapsulation layer, which covers the surface of the honeycomb skeleton filled with the high atomic number radiation shielding nanoparticles, forming a closed honeycomb shell structure.

2. The radiation shielding material with honeycomb confinement according to claim 1, characterized in that, The nanofiber network is composed of polymeric materials compatible with cross-linked polyethylene, specifically including a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer.

3. The radiation shielding material with honeycomb confinement according to claim 1, characterized in that, The high atomic number radiation shielding nanoparticles are bismuth oxide nanoparticles, and the average particle size of the nanoparticles is 20nm-200nm.

4. The radiation shielding material with honeycomb confinement according to claim 1, characterized in that, The thickness of the cellular confinement structure layer is 20μm-100μm, and the pore size of the cellular unit is 5μm-50μm.

5. A method for preparing a radiation shielding material with a cellular confinement as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Prepare a cross-linked polyethylene insulation layer; S2. Construct a honeycomb skeleton layer on the surface of the cable insulation layer; S3. Fill the honeycomb cells of the honeycomb skeleton layer with high atomic number radiation shielding nanoparticles. S4. The filled honeycomb skeleton is encapsulated to form a closed honeycomb shell structure.

6. The method for preparing the radiation shielding material with honeycomb confinement according to claim 5, characterized in that, In step S1, an insulating layer is prepared by extrusion, in which crosslinkable polyethylene material is extruded onto the surface of the conductor and then crosslinked. The extrusion temperature is 160-190°C.

7. The method for preparing the radiation shielding material with honeycomb confinement according to claim 5, characterized in that, In step S2, a honeycomb skeleton layer is constructed using electrospinning technology. The conditions for electrospinning technology are: applied voltage of 20kV, spray distance of 15cm, propulsion speed of 0.75mL / h, relative humidity of 70%, and a patterned collection device with a micropore array is used to induce the formation of a regular honeycomb unit structure.

8. The method for preparing the radiation shielding material with honeycomb confinement according to claim 5, characterized in that, S3 specifically includes: S301. Disperse bismuth oxide nanoparticles in an organic solvent and add a dispersant to form a suspension; S302. Immerse the product obtained in S2 into the suspension and dry it.

9. The method for preparing the radiation shielding material with honeycomb confinement according to claim 5, characterized in that, In step S4, the encapsulation process is carried out at a temperature of 100°C, a pressure of 3 MPa, and a time of 8 minutes.

10. The method for preparing the radiation shielding material with cellular confinement according to claim 5, characterized in that, The raw material for the honeycomb skeleton layer is a mixture of low-density polyethylene and ethylene-vinyl acetate copolymer, wherein the mass ratio of low-density polyethylene to ethylene-vinyl acetate copolymer is 7:

3. The total mass fraction of the mixture of low-density polyethylene and ethylene-vinyl acetate copolymer in the spinning solution used to prepare the honeycomb skeleton layer is 8%-15%.